2008
DOI: 10.1109/lgrs.2008.915746
|View full text |Cite
|
Sign up to set email alerts
|

A Cutoff Invariant Two-Scale Model in Electromagnetic Scattering From Sea Surfaces

Abstract: The two-scale model (TSM) is one of the most frequently employed approaches in scattering from multiscale surfaces such as ocean surfaces. It consists of combining geometrical optics (GO) with the small-perturbation model (SPM) to be able to cope with both the small-and large-scale components of the surface. However, well-known shortcomings of this method are the arbitrariness of the dividing scale and the sensitivity of the scattering cross section to the choice of this parameter. We propose to replace SPM wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 14 publications
0
52
0
Order By: Relevance
“…The U-WCA scattering model [22] belongs to the family of so-called "unified models" [32], such as the Two Scale Models (TSM) [6,33] or the Small-Slope Approximation [34], that is models which …”
Section: The Universal Weighted Curvature Approximation Scattering Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The U-WCA scattering model [22] belongs to the family of so-called "unified models" [32], such as the Two Scale Models (TSM) [6,33] or the Small-Slope Approximation [34], that is models which …”
Section: The Universal Weighted Curvature Approximation Scattering Modelmentioning
confidence: 99%
“…The U-WCA scattering model [22] belongs to the family of so-called "unified models" [32], such as the Two Scale Models (TSM) [6,33] or the Small-Slope Approximation [34], that is models which are able to cope with both large scales and small ripples at the sea surface. The U-WCA model leads to non-trivial roughness-dependent PR but has the considerable advantage of a simple formulation involving the nominal incidence angle only and requiring no facet decomposition.…”
Section: The Universal Weighted Curvature Approximation Scattering Modelmentioning
confidence: 99%
“…In this regime, the dependence of the results on the choice of k d is weak, so that the choice k d = k/5 was applied in their model. Soriano et al [29] claimed that the dependence on the choice of k d could be eliminated if the SPM is replaced by the firstorder SSA in the two-scale combination. The influence of k d on the BFTSM responsible for the Bragg scattering is discussed in Fig.…”
Section: Slope-deterministic Facet Model (Sdfm)mentioning
confidence: 99%
“…Cox and Munk showed that the surface slope distribution is non-Gaussian, and introduced the Cox-Munk model [9]. Recently, Soriano et al [10] replaced SPM with the small slope approximation to treat the small-scale roughness in the classical two-scale model, avoiding the difference brought by adopting different frequency cutoff. But for the crucial surface skewness correction, there has been no published paper since Wang et al [11].…”
Section: Introductionmentioning
confidence: 99%